City and country in Pisidia from classical antiquity to the middle ages : Ariassos, Sia and their territories - Robinson, T (2002)
This thesis provides a study of the growth and decline of two small Pisidian urban settlements, Sia and Ariassos, with an especial focus on the relationship, both social and economic, between town and country. The thesis addresses the subject primarily chronologically, although chapter two is diachronic. The first chapter provides an historical and geographical introduction to the subject. The complexities of the ethnic and cultural environment in which the two cities were founded are discussed along with the history of early settlement in the region. The succeeding chapters present, discuss and analyse the archaeological evidence for the growth, transformation and, ultimately, the decline of the settlements. The central argument of the thesis is that the settlements can only be understood if seen both within their local physical and social environment and their larger political environment. The settlements existed as part of a complex urban and rural network. The effects of the changes of the third century AD, the arrival of Christianity, tax reforms and social unrest are all explored. The thesis concludes that the image of uniformity and continuity in this mountainous region can be highly deceptive. During the period in which the Pisidian urban landscape grew, flourished and then disintegrated, the area was subject to an enormous variety of changes, social, political and economic, all of which have to be taken into account when attempting to understand the complexity of the process of urban change.